A femtosecond pulse erbium fiber laser incorporating a saturable absorber based on bulk-structured Bi2Te3 topological insulator - Lee, Junsu; Koo, Joonhoi; Jhon, Young Min; Lee, Ju Han (Optical Society of America, 2014)
We experimentally demonstrate the use of a bulk-structured Bi2Te3 topological insulator (TI) as an ultrafast mode-locker to generate femtosecond pulses from an all-fiberized cavity. Using a saturable absorber based on a mechanically exfoliated layer about 15 mu m thick deposited onto a side-polished fiber, we show that stable soliton pulses with a temporal width of similar to 600 fs can readily be produced at 1547 nm from an erbium fiber ring cavity. Unlike previous TI-based mode-locked laser demonstrations, in which high-quality nanosheet-based TIs were used for saturable absorption, we chose to use a bulk-structured Bi2Te3 layer because it is easy to fabricate. We found that the bulk-structured Bi2Te3 layer can readily provide sufficient nonlinear saturable absorption for femtosecond mode-locking even if its modulation depth of similar to 15.7% is much lower than previously demonstrated nanosheet-structured TI-based saturable absorbers. This experimental demonstration indicates that high-crystalline-quality atomic-layered films of TI, which demand complicated and expensive material processing facilities, are not essential for ultrafast laser mode-locking applications. (C) 2014 Optical Society of America